Volume 4: Heat Transfer; Electric Power; Industrial and Cogeneration 1998
DOI: 10.1115/98-gt-189
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Flow in a 180 Deg Sharp Turning Duct With Different Divider Thicknesses

Abstract: The effect of divider thickness on fluid flows in a two-pass smooth square duct with a 180 deg straight-corner turn is an important issue to the turbine blade internal cooling but has not been explored in the past. Laser-Doppler velocimetry measurements are thus presented for such a study at a Reynolds number of 1.2 × 104 and dimensionless divider thicknesses (Wd*) of 0.10, 0.25, 0.50. Results are presented in terms of various mean velocity components in two orthogonal streamwise planes and three cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Only a few studies focused on the effect of controllable parameters on the structure of the flow. Liou et al (1999Liou et al ( , 2000 experimentally showed that the divider thickness (the thickness of the structure between the inflow and outflow channels) mainly influenced the intensity and uniformity of turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies focused on the effect of controllable parameters on the structure of the flow. Liou et al (1999Liou et al ( , 2000 experimentally showed that the divider thickness (the thickness of the structure between the inflow and outflow channels) mainly influenced the intensity and uniformity of turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…The cooling air flows through a complicated serpentine passage inside the blade that comprises of several channels along the blade height with the adjacent channels connected by sharp 180 • bends. Many other applications such as the hot gas manifold of the space shuttle main engine power head (Kwak, 1986) and ventilation piping systems (Liou, 1999) involve two adjacent ducts connected by a 180 • bend. The space constraints in coolant blade passages dictate a small radius of curvature for the 180 • turn, often smaller than the hydraulic diameter.…”
Section: Introductionmentioning
confidence: 99%
“…Flow fields in such sharp 180 • bends comprise of the turning geometry: induced secondary flow, flow separation, re-circulation, and reattachment. This results in noticeable effects on the pressure loss and non-uniformity in heat transfer distributions (Liou, 1999). Hence, the design of the cooling passages involving sharp 180 • bends requires detailed knowledge of the flow resistances offered by the cooling passages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation